If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (a + 3b) * x + (a + 3b) * y = 0 Reorder the terms for easier multiplication: x(a + 3b) + (a + 3b) * y = 0 (a * x + 3b * x) + (a + 3b) * y = 0 (ax + 3bx) + (a + 3b) * y = 0 Reorder the terms for easier multiplication: ax + 3bx + y(a + 3b) = 0 ax + 3bx + (a * y + 3b * y) = 0 ax + 3bx + (ay + 3by) = 0 Reorder the terms: ax + ay + 3bx + 3by = 0 Solving ax + ay + 3bx + 3by = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3bx' to each side of the equation. ax + ay + 3bx + -3bx + 3by = 0 + -3bx Combine like terms: 3bx + -3bx = 0 ax + ay + 0 + 3by = 0 + -3bx ax + ay + 3by = 0 + -3bx Remove the zero: ax + ay + 3by = -3bx Add '-3by' to each side of the equation. ax + ay + 3by + -3by = -3bx + -3by Combine like terms: 3by + -3by = 0 ax + ay + 0 = -3bx + -3by ax + ay = -3bx + -3by Reorder the terms: ax + ay + 3bx + 3by = -3bx + 3bx + -3by + 3by Combine like terms: -3bx + 3bx = 0 ax + ay + 3bx + 3by = 0 + -3by + 3by ax + ay + 3bx + 3by = -3by + 3by Combine like terms: -3by + 3by = 0 ax + ay + 3bx + 3by = 0 The solution to this equation could not be determined.
| 8b+3b-6=38 | | 0.6666666666x-4=10 | | -2x+8=-6+5 | | -2(-10)-y=16 | | x+y=630 | | 6s-2=5s+10 | | 12-.6x=-27 | | (16x+5y)dx+(3x+y)dy=0 | | x*x=-36 | | 2x^3-8x^2-14x= | | 10x=4.09 | | n^3-n-3360=0 | | e^1-7x=9 | | (6-v)(3v-4)=0 | | x=2600 | | x-.2=13000 | | x*x=5 | | 4x+1=25-2x | | 15o^2+36o+17=0 | | ln(3x)=5.82 | | y^2+-3y+-40=0 | | 4.9(x+5.1)=36.8 | | -6n=54 | | -9+n=-8 | | 11x-2=3x+11 | | o^2+0o+-4=0 | | -7=p-5 | | 6s^2+3s=0 | | 802.1-4.82+9= | | y-9=-19 | | 4r^2+30r+10=0 | | 24=4n |